Peran Caregiver Keluarga dalam Home Care Anak dengan Penyakit Kronis: Scoping Review - Damal Lambok Simatupang; Widia Sari; Kartini Kartini; Kiki Amanda Fatmawati (Jurnal Ners, 2026)
Chronic diseases in children require long-term care that depends not only on professional healthcare services but also on the active involvement of family caregivers in home care implementation. The complexity of care requires caregivers to perform various roles that influence the quality of care and children’s well-being, while comprehensive studies regarding these roles remain limited. This study aimed to identify and synthesize scientific evidence regarding the role of family caregivers in home care for children with chronic diseases. This study employed a literature review design using a scoping review approach through the identification, selection, and analysis of relevant scientific articles. Data were analyzed using thematic narrative synthesis based on caregiver role dimensions, factors influencing role effectiveness, and the impact of caregiving on caregiver well-being. The review of 15 articles revealed that family caregivers performed four major roles, including physical roles, psychological roles, educational roles, and social and healthcare coordination roles. The effectiveness of caregiver roles was influenced by knowledge and skills, psychological conditions, social support, and access to healthcare services. Intensive caregiving activities also contributed to physical, psychological, social, and financial burdens among caregivers. In conclusion, family caregivers play an essential role in ensuring the continuity of home care for children with chronic diseases; therefore, systematic support through education, training, and family-centered healthcare services is needed.